Pemaknaan Prokrastinasi Akademik Pada Mahasiswa Semester Akhir Di Universitas Muhammadiyah Surakarta - Burhani, Ita Ipnu, Prof. Dr. Kumaidi, MA (2016)
The student is the main character in the formation of academic culture that wants to do the creative process, rather than just being an agent of change and the sheer tongue connector. Academic procrastination phenomenon generally occurs due to a tendency to delay the start, execute, and terminate an activity, so the academic procrastination is defined as prokrastinasi that occur in the academic environment. This research aims to understand and describe how the definition of academic procrastination at the end of the semester students who had taken a thesis at the Muhammadiyah University of Surakarta. Data collection tools and methods used in this study using qualitative phenomenology with interviews and observations, as well as documentation as evidence in order to strengthen the data. Methods of data analysis used data analysis is inductive. The results of this research show that six informants all understand and can description procrastination as a deed putting off work that should have been resolved. The form action is visible from the entirety of the informant is all have and choose to actively taking part in off-campus which is time-consuming. Factors affecting procrastination of academic actions caused by internal and external factors, four informants stated the delay exposed by their lazy and have some fun with his friend which means the subject still feel comfortable and are reluctant to take off his status as a student, two other informants expressed the feeling don't have the desire for immediate graduation because it hasn't had a view to where you wish to work soon or want to do other activities based on this, from the viewpoint of informants who argued that students who graduated are not necessarily going to work soon. External factors affecting the environment are informants in General does not support to complete the thesis. The influence of the environment according to the informants is an invitation-an invitation to procrastinate or task list and others that come from a different or others cost.